Предмет:
МатематикаАвтор:
анонимВычислим значение выражения (5 * 10^(-2) - 3 * 5^(-1))/10^(-2).
(5 * 10^(-2) - 3 * 5^(-1))/10^(-2) = (5 * 10^(-2) - 3 * 1/5)/10^(-2) = (5 * 10^(-2) - 0,6)/10^(-2) = (5 * 0,01 - 0,6)/0,01 = (0,05 - 0,6)/0,01 = -0,55/0,01 = -55 * 0,01/(1 * 0,01) = -55/1 = -55;
В итоге получили, (5 * 10^(-2) - 3 * 5^(-1))/10^(-2) = -55.
Автор:
cosmodayДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть